Intervention Trial of Microalbuminuria in T2DM with Antioxidant, Antithrombotic and ACE Inhibitor Agents - Zulfikar, Ali M; Ali, SMK; Khan, AK Azad; Ali, Rumana (Bangladesh Medical Journal, 2009)
The present study was undertaken in T2DM patients aged between 40 and 50 years, from outpatient department (OPD) of BIRDEM Hospital, Shahabagh, Dhaka. A total of 1605 T2DM patients examined, 390 were found microalbominuric (ì-albumin >30mg/g) giving a prevalence rate were 22.92%. and nonmicroalbuminuric (ì-albumin d"30 mg/g). The microalbuminuric subjects were put on intensive intervention with ACE inhibitor (Captopril 25 mg, twice daily), Antioxidant (Vitamin C- 200 mg, Vitamin E- 50 mg and Vitamin A- 6 mg daily), and Antithrombotic (Aspirin- 75 mg daily). Both microalbuminuric and nonmicroalbuminuric subjects were put on strict diet control and antidiabetic therapy. The following tests FBG, HbA1c, BP, T-Cholesterol, HDLc, ì-albumin, ACR, were done in both groups at 3 months intervals up to 18th months. The mean (years) ±SD age were 45.67 ± 3.98, and 45.45 ±3.94 and duration of diabetes 3.78 ± 3.14 and 3.72±3.07 in microalbuminuric and nonmicroalbuminuric subjects respectively. The microalbuninuric group showed satistically significant difference (p<0.005) in the following parameters FBG, HbA1c, SBP, T-choles, ACR, U.Creatinine in comparison to nonmicroalbuminuric group. Nonmicroalbuminuric subjects showed the deterioration in TG, HDLc, and a conversion rate of 21.7% from nonmicroalbuminuric to microalbuminuric. The present intervention with ACE inhibitor, antioxidant and antithrombotic improved glycaemic control, lipid profile and renal functions by 68% in microalbuminuric T2DM subjects. DOI: 10.3329/bmj.v37i2.3589 Bangladesh Medical Journal 37(2) 2008 30-36